Integritas Banser Kabupaten Nganjuk Dalam Prinsip NKRI Harga Mati: Sebuah Perspektif Cultural Theory - Arif, Muhammad; Darwati, Yuli (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2022)
Abstrak Banser is a semi-autonomous body of the Ansor Youth Movement of the largest mass organization in Indonesia, namely Nahdlatul Ulama'. Banser has a field of assignments related to the field of social religion which is more practical and strategic. Regeneration in Ansor and Banser bodies is held every week, and continues to be ongoing in order to prepare new cadres. Regeneration must be carried out actively and programmed in accordance with the vision and mission that has been set. Distribution and independence continues to be carried out in stages. This vision and mission will continue to be realized over the next few years in order to form massive integrity and make a major contribution to all Indonesian people. So that a principle can be formed that is very strongly internalized within Banser's body, namely